Studying the biochemical composition of peanut accessions from the VIR collection - V. D. Bemova; T. V. Shelenga; M. Sh. Asfandiyarova; T. V. Yakusheva; N. V. Kishlyan (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. Peanut is one of the most important oil crops for food purposes. Natural peanut butter contains two unsaturated fatty acids, oleic and linoleic, which make up to 80% of the total fatty acid content in peanut oil. The quality of oil depends on the ratio between these two acids. Analyzing the diversity of oil content and fatty acid composition in peanut accessions preserved at VIR and assessing the effect of soil, climate, and other factors on these characters is vital for the development of new peanut cultivars rich in oil. Materials and methods. Peanut germplasm accessions were studied for their biochemical composition of fatty acids and the content of oil and protein. The accessions were reproduced for three years (2019–2021) at two ecogeographic locations: in Krasnodar Territory, and Astrakhan Province. Cv. ‘Otradokubansky’ was used as a reference. ANOVA was applied for statistical data processing. Results and discussion. The percentage composition of 18 fatty acids was calculated in peanut oil, with oleic and linoleic acids dominating. The content of oleic acid depended on the genotype for 42–53%, and that of linoleic acid, for 50–71%. The latter was also influenced by the place and year of cultivation. The ranges of variation over the three years of studies in Krasnodar Territory were 35.4–57.6% for oleic acid, and 18.3–38.1% for linoleic acid, whereas in Astrakhan Province they were 33.4–51.2%, and 30.9–42.7%, respectively. Under unfavorable conditions, the content of oleic acid in peanut prevailed. The oil content depended on the genotype for 81%, and its percentage was 32.0–44.4%.